The assessment of fungal bioaerosols in the crypt of St. Peter in Perugia (Italy). (March 2015) - Ruga, L.; Orlandi, F.; Romano, B.; Fornaciari, M.
Abstract: The inspection of the quality of the indoor air in which a work of art or a historical artefact is kept becomes essential for its conservation. The determination of organic pollutants represents an important tool in pre-emptive conservation. The study investigated the quality of the air in the crypt of the Basilica of St. Peter in Perugia (Italy) through different methodologies. The objectives included the analysis of the levels of biological particulates of fungal origin, and the determination of the degree of variability of the airborne spore concentrations, as indicative of the level of contamination of the environment. The quantitative analysis of the airborne fungal component demonstrates that across the whole period considered there were wide variations in the bioaerosols, heterogeneous spore distributions and different peak concentrations in the areas studied. The qualitative analysis of the airborne fungal component allowed the determination of the different fungal genera present, both in the interior of the crypt and in the outside environment. The analysis of the data shows an increasing trend over the period considered, with the highest values during the months of June and July. Highlights: The total fungal spores counting give a first approximation of air contamination. The indoor air quality inspection is essential for the work of art conservation. Heterogeneous spore distributions and concentration peaks were recorded in the crypt. The study shows a spore increasing trend above all during the months of june and july. Air qualitative analysis allowed the determination of numerous fungal strains.